The effect of body condition on pregnancy in sheep - Bácsi, Eszter Ilona; Egerszegi, István; Rózsáné Várszegi, Zsófia; Klein, Renáta; Jávor, András; Oláh, János (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
The oestrus of ewes, their ovulation rate, and the ability to raise the fetus are properties determined by several genes, as well as these traits’ heritability value is low. Because of this, other factors (e.g.: climatic conditions, feeding, body condition) greatly influence them. Among these, the body condition is perhaps one of the most decisive factors in pregnancy. Determination and scoring of body condition are rarely used in our country. It is very important from the point of view of fertility, as it affects not only the conception rate of ewes, but also the number of twin lambs. In the experiment we measured the fat thickness and body weight of summer period oestrus synchronized ewes and then mated sheep, and scored their body condition. We did this to determine the correlation between these parameters in the herd we examined with the pregnancy of the sheep and the number of twin lambs, and whether there is a difference between the different breeds/genotypes. We found significant differences in body weight and body condition score between the genotypes, and at the second measurement, the difference was already detectable in the subcutaneous fat depth. The average fat thickness of White Dorper x White Suffolk F1 sheep was 3,99 mm while increase of Dorper, and White Dorper breeds these data were significantly lower. The results presented here are part of a research, it is a preliminary founding, since the lambing period has not yet started, furthermore a larger number of investigation and measurements will be necessary for a full evaluation of the topic.